Strategic Information Needs (SIN) based on Demographic and the Regional Competitiveness Index in Supporting Public Library Services to Achieve SDGs (Comparative Study in Seven Provinces with the Highest RCI/IDSD Scores in Indonesia) - Widiyawati, Anita Tri; Kwiecien, Kanyarat; Nguyen, Lan Thi (Universitas Wijaya Kusuma Surabaya, 2026)
Purpose Research. The uneven distribution of demographic characteristics and regional competitiveness across Indonesian provinces creates structurally differentiated information needs that existing public library services have yet to address systematically. Although the Regional Competitiveness Index (RCI/IDSD) developed by BRIN provides a comprehensive twelve-pillar framework for assessing regional development performance, no prior study has integrated this instrument with demographic analysis to map strategic information needs comparatively across high-performing provinces, leaving a critical gap in both theoretical and policy literature on information services within decentralized governance contexts. Research Method. This study employed a qualitative descriptive design combining document analysis and comparative analysis. Secondary data is drawn from demographic data of each province from the Central Statistics Agency, IDSD data from BRIN in 2025, and supporting peer-reviewed literature. Data collection was followed by content analysis, the construction of a structured comparative matrix, typological clustering, and interpretive synthesis. Analysis Data. Data were analyzed in three sequential stages: content analysis, comparative and typological analysis, and strategic synthesis, validated through source triangulation and standardized conceptual categories. Results. Four distinctive typologies emerged: Metropolitan Formal, Tourism-Cultural, Urban Buffer, and Agrarian-Inclusive, each corresponding directly to measurable SDG attainment gaps across SDGs 1, 2, 3, 4, 8, 9, 10, 11, and 17. At the same time, SDG 6, 7, 13, 14, and 15 remained unreachable due to IDSD's inherent environmental blind spots. Conclusion. Strategic information needs are systemically differentiated, requiring asymmetric library interventions. Future research should develop a library-readiness index that integrates all 12 IDSD pillars and incorporates environmental indices to achieve holistic coverage of the SDGs. Keywords: Information Needs; Regional Competitiveness Index; Demographic Analysis; Public Library; Sustainable Development Goals